Quality of life and its demographic predictors among workers at a plastic factory in Malaysia: a cross-sectional study - Asem Iyad Ahmed Alnabih; Belal Aldabbour; Mohd Faizal Mat Tahir; Nor Kamaliana Khamis (Intelektual Pustaka Media Utama, 2022)
Quality of life (QOL) is an individualized measure that reflects a person’s subjective feelings towards the different aspects of his or her life and incorporates them into his overall health evaluation. The WHOQOL-BREF is a QOL measurement tool that has been validated in worldwide and local studies, with good reliability and sensitivity. WHOQOL-BREF questionnaire was used to evaluate the QOL of 89 workers at a plastic factory in Selangor, Malaysia. These were compared using t-test and Spearman’s bivariate correlation test to assess for significant correlations and predictors of performance in the different domains. The performance of the sample, both overall and for individual domains, was significantly lower than reported in previous studies. Local workers, highly educated workers, workers with shorter employment, and workers who did not take overtime performed significantly better than their respective counterparts. Also, lower education, foreign nationality, longer employment at the factory, overtime, and crushing jobs were associated with lower QOL scores. Studies evaluating QOL in industrial workers in Malaysia are scarce. Our sample is more diverse than the previous similar studies from Malaysia, and hence it offers new insights into the QOL of plastic industrial workers in the country.